PAYBACK PERIOD ANALYSIS OF DISTANCE MASTER EDUCATION IN INDONESIA - Kurniatun, Taufani; Rosita, Tita; Rusyani, Erni (Faculty of Economics and Business, University of Pasundan, 2023)
Research on the rate of return on the learning process in distance higher education aims to measure the level of learning investment in post graduate program distance education. The method used in this research is descriptive research with a quantitative approach. The research instruments distributed were to alumni of the Terbuka University Postgraduate Program spread across various cities, including the cities of Bandar Lampung, Bandung, Batam, Bogor, Jakarta, Jember, Malang, Medan, Padang, Palembang, Samarinda, Semarang, Serang, Sorong, Surabaya, and Surakarta. As many as 116 respondents from the total population of 395 alumni (using stratified random sampling technique) made up the study sample of 116 respondents. The results of the study show that investment in education using the payback period method is feasible.